Impacts of Vitamins and Minerals in Animal Reproduction - Verma, Ranjeet; Biswal, Jyotsnarani; Kennady, Vijayalakshmy; Rahman, Habibar (2020)
Nutrition has an important impact on the reproductive performance of animals. Specific nutrients and dietary ingredients have been implicated on reproduction in animals. Essential trace minerals and vitamins play a vital role in many enzymatic and metabolic pathways that are critical for reproduction in livestock species. The conceptus relies entirely on the maternal system for a sufficient supply of trace minerals and other nutrients needed for normal development. If the supply is inadequate, growth and/or health of the conceptus can be affected adversely, and many of these effects carry over into the neonatal period. Hence, the proper supplementation of trace minerals and vitamins is highly desired to maintain normal reproductive function of the livestock. The present review aims in detailing different roles of specific vitamins and minerals in animal reproduction.